2011
DOI: 10.1007/s00595-010-4393-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique for closing a tracheocutaneous fistula using a hinged skin flap

Abstract: We present the case of a 73-year-old man with successful closure of a persistent tracheocutaneous tissue defect that resulted from poor wound healing after a temporary tracheostomy was performed during treatment for drug-induced anaphylactic shock. We repaired the tracheal defect using a cutaneous flap with its cutaneous surface positioned to cover the tracheal lumen. The advantage of our method is that it minimizes the suturing required and results in fewer problems with anastomotic insufficiency. This is a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
20
0
2
Order By: Relevance
“…Al comparar las técnicas de cierre de traqueostomas persistentes, presentan similares resultados en cuanto a tasas de éxito y complicaciones asociadas [6][7][8] . Teóricamente, se han descrito beneficios para la fistulectomía con curación por segunda intención en lo que respecta al menor tiempo quirúrgico 7,8,11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al comparar las técnicas de cierre de traqueostomas persistentes, presentan similares resultados en cuanto a tasas de éxito y complicaciones asociadas [6][7][8] . Teóricamente, se han descrito beneficios para la fistulectomía con curación por segunda intención en lo que respecta al menor tiempo quirúrgico 7,8,11 .…”
Section: Discussionunclassified
“…), el cierre espontáneo del traqueostoma puede verse dificultado en algunos casos, persistiendo la fís-tula traqueocutánea luego de la decanulación 3,4 . En general, la literatura es bastante escasa sobre la ocurrencia de esta complicación en adultos 5 , sin embargo se describe que los índices varían entre 3,3% y 29% 6 . Esta situación se produce debido a la epitelización escamosa del trayecto fistuloso 7 , el cual puede verse asociado a complicaciones como infección, dificultad en la fonación, irritación de la piel y problemas tanto estéticos como sociales para el paciente 8 .…”
Section: Introductionunclassified
“…[5][6][7][8][9] The epithelial layer of the hinged flap will eventually be replaced with a mucosal layer. 6 Even though with invagination of two hinged turnover flaps into the fistula, using multiple layered sutures, it is possible to avoid narrowing the tracheal lumen. In addition, the strength of this closure could be disrupted by a sudden elevation of airway pressure such as that which accompanies paroxysmal coughing.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] These include multiple layered primary closure with partial fistulectomy, 3 bipedicle delayed flap closure with primary inversion of the edges of the fistula (fistulectomy with healing by secondary intention), 1 closure by transplantation of an ear cartilage graft with muscle and fasciocutaneous flaps, 4 and elevation and inward rotation of the epithelial lining of the tracheocutaneous fistula as a marginal flap, using a hinged turnover flap, with an additional V-Y advancement flap. 2,[5][6][7][8][9] It has been reported that primary closure with excision of the fistula tract down to the level of the trachea may result in tracheocele, pneumopericardium, pneumothorax, and pneumomediastinum. 1,2,[10][11][12] Closure with a turnover flap of skin and fibroadipose tissue means that the defect in the tracheal lumen is covered by the outer surface of the cutaneous flap.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many variations of primary closure have been developed and claim to reduce risks while maintaining cosmetic benefit and convenience; however, large and long-term studies of such methods are absent. [11][12][13][14][15][16] We have previously compared the 2 methods of TCF closure at our institution and found no significant differences in risks or efficacy between primary closure and secondary intention. 9 Shortly after this study was published, we experienced 2 serious complications using the primary closure method.…”
mentioning
confidence: 97%